Graphical modelling framework development to identify the control system complexity associated with the continuous processes based on ISA-TR106.00.01-2013 and ISA-TR106.00.02-2017 for omnicon S.A. (2019)
The activity of graphical modelling in industrial process is indispensable because it allows the process engineers to understand, define, quantify, visualize, or simulate by referencing it to existing and usually commonly accepted knowledge. Nowadays the graphical modelling has been used in the industrial field for material flow or process behavior design. As soon as the application of automation technologies has been increasing in industrial process, it became necessary to adapt the activity of modeling to automation functionalities and offer a specific utility for process engineers to allow them to make decisions based on quantified information. This monograph explains the development of a graphical modeling framework intended to offer a quick overview of the control system complexity associated to continuous processes based on international society of automation standard. It does not exist a modelling approach that captures these aspects in a unified framework. The graphical modelling framework focuses only on continuous processes and is expected to bring value in the facilities of Omnicon client.